2007
DOI: 10.1097/meg.0b013e3282202bca
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infliximab on circulating levels of leptin, adiponectin and resistin in patients with inflammatory bowel disease

Abstract: Serum levels of leptin and adiponectin had no significant alterations, whereas serum-resistin levels are significantly decreased after infliximab therapy in IBD patients, suggesting a possible proinflammatory status for resistin in IBD and a role as a marker of successful therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 37 publications
2
37
0
2
Order By: Relevance
“…11 12 Consistent with our fi ndings, most previous studies found no effect of TNF inhibition on circulating adiponectin levels in RA. 37 44 45 Other studies have suggested an increase in adiponectin levels, 46 47 in the absence of an effect on mRNA adiponectin levels in subcutaneous fat biopsies. 47 Together, the effects of TNF inhibition on adiponectin levels are at present poorly understood.…”
Section: Decrease In Visfatin Serum Levels Is Associated With Improvementioning
confidence: 97%
See 1 more Smart Citation
“…11 12 Consistent with our fi ndings, most previous studies found no effect of TNF inhibition on circulating adiponectin levels in RA. 37 44 45 Other studies have suggested an increase in adiponectin levels, 46 47 in the absence of an effect on mRNA adiponectin levels in subcutaneous fat biopsies. 47 Together, the effects of TNF inhibition on adiponectin levels are at present poorly understood.…”
Section: Decrease In Visfatin Serum Levels Is Associated With Improvementioning
confidence: 97%
“…These results are consistent with previous reports showing that serum resistin levels are correlated with markers of infl ammation in patients with RA. 36 37 We are the fi rst to report altered resistin levels after long-term treatment with GC. As resistin is mainly produced by macrophages 8 38 and a decrease in the number of macrophages in synovium is consistently associated with improvement after effective treatment in RA, 39 40 we hypothesise that the observed reduction in resistin levels may refl ect the decreased number of synovial macrophages.…”
Section: Contributorsmentioning
confidence: 99%
“…In addition, resistin correlated with the disease activity score, white blood cell count, and CRP in patients with Crohn's disease [121,122]. In contrast to leptin and adiponectin, resistin significantly decreases after TNF-α blocking therapy in patients with inflammatory bowel diseases and has been proposed as a marker of successful therapy, similar to the patients with rheumatoid arthritis [123].…”
Section: Resistin and Inflammatory Bowel Diseasesmentioning
confidence: 99%
“…Resistin has been suggested as an independent predictor of disease activity in patients with inflammatory bowel disease and has been proposed as a marker of successful therapy [121,123]. Moreover, RELM-β has anti-parasitic effects and may play a role in the pathology of inflammatory bowel diseases.…”
Section: Resistin and Inflammatory Bowel Diseasesmentioning
confidence: 99%
See 1 more Smart Citation